Effect of Mastery Learning Combined with Mind Mapping Technique on the Students’ Sculpture Performance Ability for Junior University Students - Qingsong, Xu; Karanyathikul, Angkana; Kotchasit , Sombat (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aims: The Chinese government has issued a series of policy documents to support the development of the cultural industry, providing policy guarantees and guidance for the development of sculpture education. Traditional teaching methods usually use unified teaching content and teaching methods, which cannot meet the individual needs of students. The comprehensive application of "Mastery Learning with Mind Mapping" theory and methods can provide solid technical support and rich teaching methods for the reform of sculpture education. Through the application of personalized learning plans and mind mapping, students' learning content and space can be expanded, and their learning efficiency and learning quality can be improved. This comprehensive approach can not only meet students' learning needs but also stimulate their learning interest and creativity and promote their all-round development. Therefore, the promotion and application of this method in sculpture education are of great significance and value. This study aims to explore and evaluate the impact of mastery learning combined with mind mapping technique on college students' sculpture learning achievements and performance ability through mastery learning combined with mind mapping technique. Materials and Methods: The instruments for the experiment were four lesson plans. To evaluate the quality of a curriculum plan, it can be assessed using a Likert five-point scale. The quality of the scale can be measured using the Item-Objective Congruence (IOC) The assessment process involves analyzing each component of the lesson plan, attributing scores on the Likert scale, and then calculating the average score and the standard deviation (SD) for each component. The instruments for collecting data were two instruments needed to collect the sampling data, as the detailed list showed: sculpture score assessment and sculpture performance competency assessment. The sample was 30 students (one class) among the 120 junior students in the 2023 academic year. The procedures for data collection are as follows, the sample learning achievement before and after learning through Mastery Learning with Mind mapping and sculpture performance ability after learning through Mastery Learning with Mind mapping with the established 70 percent Results: The study evaluated the effectiveness of employing mastery learning combined with mind mapping techniques to enhance students' learning achievement and sculpture performance ability. Significant improvement was observed, with posttest scores surpassing pretest scores (t =13.06*, p =0.05). Furthermore, students' sculpture performance ability scores after mastering learning with mind mapping (81.1%) exceeded the 70% criterion, with statistical significance (t =11.05*, p =0.001). Conclusion: Compared with previous related studies, the results of this study showed that using mastery learning combined with mind mapping technique teaching had a significant positive effect on the sophomore research on sculpture performance ability. This is consistent with the findings of Chen Linsheng (2022), who found that the use of mind-mapping techniques in art education can improve students' learning achievement. Combining the findings of previous studies and the results of this study, we can conclude that mastery learning combined with mind mapping technique teaching has positive effects on the ability of sculpture performance in sophomore students. However, further research still needs to explore the impact of different teaching methods on students of different grades and specialties to get a more comprehensive understanding of the effects of mastery learning combined with mind-mapping technique teaching.